Human Relations Head of Madrasah in Improving Teacher Performance at Madrasah Aliyah Nurul Huda Bantar Gebang - Afandi, Dedi; Kuswandi, Aos; Aprilliantoni (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to analyze the implementation of Human Relations for Madrasah Principals in Improving Teacher Performance at Madrasah Aliyah Nurul Huda, and present the obstacles encountered in implementing Human Relations for Principals in Improving Teacher Performance at Madrasah Aliyah Nurul Huda. The type of research uses a descriptive analysis research method, namely, a research method that describes an ongoing situation based on the actual and factual data and information obtained. The data collection techniques used are: literature study, field study, through observation, and interviews. The results of this study indicate that Human Relations in improving teacher performance refers to several points, namely (1) good communication. (2) a comfortable work environment, and (3) there is a reward from the principal. Thus, it can be seen that the obstacles to the implementation of Human Relations in improving teacher performance are, (1) differences in perceptions in receiving messages and (2) the inability of subordinates to initiate communication with the principal.